Efforts to improve information system-based residents administration services - Leonardi Paris Hasugian; Aldi Hamzah Anugrah; Poni Sukaesih Kurniati; Edo Rahmat Hidayat; Sri Dewi Anggadini; Finna Afrilia Elmanda; Selvia Lorena Br Ginting; Yogie Rinaldy Ginting (Community Empowerment, 2023)
The aim of community service at Rukun Warga 06, Antapani Wetan Subdistrict, Bandung City is to provide information system facilities to enhance the efficiency of activities related to managing residents administration. This administration involves the issuance of certificates for various purposes, ensuring transparency in residents' contributions, and providing a platform for reporting community problems or aspirations. The method employed in this service begins with problem identification, analysis to prioritize urgent needs, system development, and outreach to gather feedback from users for evaluation. The result is improved efficiency in residents administration management, enhanced transparency in contributions, and simplified reporting of problems or aspirations.